Classification method based on the diagnosis of morphological quality in nursery for the selection of promising forest species in restoration programs - Ureta Leones, Diego Armando (2018)
At present, morphological quality studies are increasingly important to select species of forest interest grown in nurseries that meet the biological requirements of the forest site. The objective of this work was to evaluate the morphological quality in nursery for the selection of promising forest species that respond favorably at the restoration of Amazonian degraded ecosystems. For this, a morphological diagnosis was made in the nursery, expressed through attribu- tes and quality indices of six forest species and a hierarchical dendrogram was used to classify groups of species according to the 11 morphological variables analyzed. The morphological diagnosis was a viable tool for forest nurseries, which allows selecting the best quality and suitable species for acclimatization to the different environmental conditions. The classification method allowed the formation of three groups of species based on morphological quality attributes and indices, the first formed by Ocotea quixos and Cedrela odorata, the second by Maclura tintoria, Myroxylum balsamun and Ochroma pyramidale and the third by Cedrelinga cateniformis. The separation of the groups was determined by the greater biomass production, degree of lignification and the low morphological quality. The species Cedrela odorata, Cedrelinga cateniformis and Ocotea quixos were of higher quality and with adequate conditions at three months of revival, which will be reflected in their posttransplant response, survival capacity and greater growth and development potential in Amazonian conditions.